Cloud-Based Genomic Data Analysis: IT-enabled Solutions for Biotechnology Advancements - Sandu, Arun Kumar; Pydipalli, Rajani; Tejani, Jayadip GhanshyamBhai; Maddula, Sai Sirisha; Rodriguez, Marcus (Engineering International, 2022)
This study explores how cloud-based genetic data analysis can advance biotechnology in a revolutionary way. The primary goals are to investigate how cloud computing and genetic analysis might be integrated, assess system performance using case studies and performance measures, and look at potential future directions and policy consequences. Methodologically, reports, case studies, and current literature were synthesized using a secondary data-based review approach. Important discoveries demonstrate how cloud-based systems can improve genomic research’s scalability, efficiency, and collaboration. However, issues to be resolved, such as the digital gap, ethical governance, and data privacy, are also important. The consequences of policy highlight the necessity of solid frameworks to protect personal information, close the digital gap, and advance moral research methods. Cloud-based genomic data analysis presents opportunities for biotechnology advancements and discoveries to be made faster. Still, it raises ethical, legal, and policy questions that must be carefully considered.